TRANSFORMATION OF STUDENT SOCIAL PRACTICES: FROM AN APPLICANT TO A STUDENT - E. L. Samarina; S. P. Avdoshina (Дискурс, 2019)
Sociological analysis of transformation trends of educational paths of high school seniors and students is presented. Satisfaction with higher education among young people in Russia and in comparison with foreign studies is examined. The article also presents the results of a longitudinal study of high school seniors and students of several Russian higher educational establishments. Defining characteristics and dominant career orientation have been studied. Russian students are generally satisfied with their choice and intend to continue their studies, although they would like to improve career guidance efficiency. Students are aware of perspectives and advantages and choose to obtain education. Most of them have no regrets concerning their choice, believe that their specialty is in demand and plan to work within their specialty.